2014
DOI: 10.1007/s00170-014-6203-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modeling of friction stir welding of stainless steel 304L

Abstract: This paper presents a numerical model, based on the displacement of one point of the material flow relative to a fixed reference point, in order to formulate the heat generation during friction stir process and thereby calculate the temperature difference between advancing and retreating sides. This model considers frictional heating dependent on both the temperature and the velocity of the tool, as well as heat generation due to plastic deformation dependent on temperature, and assumes that friction heat at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
1
19
0
2
Order By: Relevance
“…Heat partition between the tool and the workpiece Tool parts are expected to gain heat more than the workpiece during FSW due to the low thermal conductivity of DH36 steel (as received from the manufacturer = 45-55 W/m.K) compared to the tool types (PCBN) which is about three times that of steel. The partition of heat between tool and workpiece has been calculated by other researchers [2,21] as follows:…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat partition between the tool and the workpiece Tool parts are expected to gain heat more than the workpiece during FSW due to the low thermal conductivity of DH36 steel (as received from the manufacturer = 45-55 W/m.K) compared to the tool types (PCBN) which is about three times that of steel. The partition of heat between tool and workpiece has been calculated by other researchers [2,21] as follows:…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Lower plastic deformation due to the lower viscosity at the front of the tool surface has been given as a reason for this minimum temperature. Darvazi et al [21], through numerical modelling, found that the maximum temperature in FSW of stainless steel 304 L was in the back half of the shoulder region and towards the advancing side. They also found that there was more asymmetry in temperature under the shoulder compared to the regions away from it.…”
Section: Torquementioning
confidence: 99%
“…De acordo com os resultados de Darvazi and Iranmanesh [20] para a simulação térmica do aço inoxidável austenítico AISI 304L com espessura de 3,2 mm, existe um gradiente de temperatura entre a região do topo e do fundo da junta soldada, como pode ser observado na Figura 6. Tal resultado é suportado por outros estudos [21].…”
Section: Figuraunclassified
“…Distribuição de temperatura na seção transversal da solda FSW do aço inoxidável austenítico AISI 304L [20]. É possível comprovar por esta imagem o diminuto tamanho dos grãos na ZM-I.…”
Section: Figura 5 Micrografia Obtida Por Mev Operando No Modo Se Comunclassified
“…The named auto-adjusting or retractable or double-acting FSW equipment is complex and expensive. As for high melting point materials, it is almost impossible due to the limitations of pin tool design [8][9][10]. Conventional refilling methods by fusion welding technology result in a serious decrease of joint performance.…”
Section: Introductionmentioning
confidence: 99%